PENGARUH TERPAAN MEDIA SOSIAL INSTAGRAM @TOKOCRYPTO TERHADAP BRAND LOYALTY PENGGUNA(Survei Followers Akun Instagram @Tokocrypto) - Teguh Ardiansyah (2023)
In recent years, the investment in cryptocurrency assets has experienced a rapid increase. The potential for profits has attracted many individuals to participate in this investment sector. According to data from BAPPEBTI, there are now more than 17 million cryptocurrency investors in Indonesia. However, the substantial growth in user numbers must be confronted with the continuous decline in the market trend due to the global financial crisis. Amidst the challenging market conditions, the number of companies authorized to trade cryptocurrency assets continues to rise. Tokocrypto, as one of the companies with the largest user base, faces fierce competition from these companies in order to maintain brand loyalty among their users. To address this competition, Tokocrypto utilizes Instagram as a social media platform to foster relationships with its followers. The objective of this research is to determine the extent of the influence of media exposure through the Instagram account @tokocrypto on user brand loyalty. The research methodology employed is quantitative explanatory, utilizing a questionnaire survey distributed to 400 respondents who are both followers and users of the Tokocrypto application. The theoretical foundation utilized in this study is the Uses and Effects theory. Based on the analysis of the collected data, the research findings reveal a significant influence of media exposure on the Instagram account @tokocrypto on user brand loyalty, accounting for 70.2%, while the remaining 29.8% is influenced by other factors.